REVIEW OF ISLAMIC LAW ON THE FACTORS MARRIAGE DELAY CASE STUDY IN KASREMAN VILLAGE KASREMAN SUBDISTRICT NGAWI REGENCY - Muhammad Arif Abdul Azis (Pondok Pesantren Modern Islam Assalaam, 2023)
The problem of marriage has become an increasingly complex problem. Starting from the many cases of early marriage that require carrying out marriages with mental and financial unpreparedness so as to cause bad consequences in the form of divorce. Until there is a case of delay in marriage carried out by people who are actually mentally and financially ready but consciously reluctant to carry out marriage. In fact, Islam has ordered for someone who has been able to carry out marriage so that it can channel sexual desire properly and avoid adultery. This paper will examine the cases of marriage delays that occur in many youths in Kasreman Village, Kasreman District, Ngawi Regency by using deductive methods. With this method it is known that there are 4 main factors that are the background to the occurrence of marriage delays, namely customs factors, economic factors, trauma factors and factors of lack of religious understanding. Once known the delay factor of marriage it will be easier to find ways in prevention.